What the robin knows : how birds reveal the secrets of the natural world - Young, Jon, 1960- (Houghton Mifflin Harcourt, 2012)
Shares strategies for expanding one's awareness of bird communication and maintaining a non-threatening presence in natural environments, explaining the sounds and behaviors that reflect various bird warnings, feelings, and messages.